Organizational Justice and Well-Being Moderating Effects of Power Distance and Collectivism - Balbeer Singh, Satnamjeet Kaur (2005)
The employees well-being has been a growing concern amongst organizations as it would affect the employees satisfaction towards his or her jobs, and would affect an individual’s psychological and physical well being. The well-being of an employee is important as it affects the quality of an individual’s life and his or her physical and psychological well-being. The ability to promote a feeling of well-being is of considerable benefit not only to employees in the community but also to the employer’s bottom line. The psychological and physical well-being of employees and their satisfaction with their work and workplace would affect the organizational citizenship at work, and turnover rates.